How to Improve TRUS-Guided Target Biopsy following Prostate MRI - Byung Kwan Park (MDPI AG, 2021)
TRUS is a basic imaging modality when radiologists or urologists perform cognitive fusion or image fusion biopsy. This modality plays the role of the background images to add to an operator’s cognitive function or MRI images. Operators need to know how to make TRUS protocols for lesion detection or targeting. Tumor location, size, and shape on TRUS are different from those on MRI because the scan axis is different. TRUS findings of peripheral or transition tumors are not well known to radiologists and urologists. Moreover, it remains unclear if systematic biopsy is necessary after a tumor is targeted. The purpose of this review is to introduce new TRUS protocols, new imaging features, new biopsy techniques, and to assess the necessity of systematic biopsy for improving biopsy outcomes.